Pertumbuhan, Hasil dan Analisis Produksi Tanaman Jagung (Zea mays L.) yang Diperlakukan dengan Pupuk Organik dan Biourin di Lahan Kering - SUKADANA, I MADE; KARTINI, NI LUH; AMBARAWATI, I.G.A.A. (Agrotrop : Journal on Agriculture Science; Vol 3 No 1 (2013))
Growth, Yield, and Production Analysis of Maize (Zea mays L.) Treated by Organic Fertilizer and Cow Biourine in Dry Land Maize productivity in Bali is still low at around 3.4 ton/ha. Low soil fertility is one of the factors contributable to the low productivity of maize. Soil condition at the research field has low level of fertility with low levels of nitrogen and C-organic. This research aims at finding out the impact of organic fertilizers and cow biourine to the growth and yield of maize in dry land and to analyze it gross margin. Experiment was designed with randomized block design (RBD) with two factors and four replications. The dosage of the first factor namely without organic fertilizer, cow organic fertilizer 15 tonnes/ha and worm casting fertilizer 15 tonnes/ha, whereas dosage of cow biourine namely 0 liter, 1.000 liters, 2.000 liters and 3.000 liters/ha respectively for the second factor. The research results show that there is highly significant interaction (p<0.01) between organic fertilizers and cow biourine to the number of leaves aged at 21, 35, 49 and 63 dap, trunk diameter, dry matter weight/plant, number of cobs/plant, and harvest index, however it shows significant interaction (p<0.05) to leave area index (LAI) at age 35 dap and soil pH at harvest. The combination of worm casting fertilizer of 15 tonnes/ha with cow biourine 2.000 liters/ha resulted in the highest dry weight of seed/ha to 4,09 tonnes/ha, an increase of 69,71% compared to no fertilizer. The relationship between organic fertilizer and cow biourine to the dry matter yield follows a quadratic pattern, hence 15 tonnes/ ha worm casting fertilizer and 2000 liters/ha of cow biourine resulted in optimum yield from this research. Result from the gross margin analysis shows that revenue received at Rp 8.7935 million based on the price of dry shelled corn at Rp 2.150/kg does not cover the high variable cost at Rp 26.664,500.
Keywords: organic fertilizer, cow biourine, maize, dry land, gross margin